CONNECTING ARTS ACTIVISM, DIVERSE CREATIVITIES AND EMBODIMENT THROUGH PRACTICE AS RESEARCH - Burnard, PA; Jasilek, Susanne; Dragovic, Tatjana; Cook, Peter (SensePublisher, 2018)
Environmental artists are ecologically and politically motivated to change the way we view our world. Artists undertake the production of art and activism, where the art-making becomes more than art; it becomes activism; a way that allows for raising awareness; a way to retrieve, express and communicate a political message. Here, diverse creativities (including intercultural, interdisciplinary, and artistic creativity) enable forms of authorship with particular kinds of power and capacity. In this chapter, We draw on three activist enquiry practices which embody: (i) intercultural creativity through an activist choreographic practice involving a Greenlandic and Scandinavian dance company; (ii) transdisciplinary creativity through an arts-based environmental education practice inspired by an activist sculpture involving a primary school in the UK; and (ii) artistic creativity inspired by an artist activist residency practice in a Higher Education setting in the UK. Each practice features artist-researcher collaborations. Each practice involves arts as activism. Each practice makes explicit an understanding of the body as inscriptor, where the relationship between the body, power and the authoring of diverse creativities is crucial in the embodiment of arts practice as research and arts education. Each practice as research stimulates reflection and discussion by teachers, students, artists, researchers and policy makers interested in what it might mean to live the arts-as-political-as-embodiment in creating practice as research where arts activism, diverse creativities and embodiment is manifest.